Behind Every Successful Man - Wanner, Zukiswa (NB Publishers, 2021)
Nobantu has everything a girl could dream of: a brilliant businessman for a husband, two cheeky but adorable children, and two of the best friends a girl could ask for. And yet, on Nobantu's thirty-fifth birthday, surrounded by glitz, glamour and fame, she realises something important. What has happened to her ambitions? Her career? What has happened to Nobantu?...
Keywords: Fiction; Women